Dystopian Newspeak in the Translation of David Mitchell’s Novel “Cloud Atlas”: Lexical and Morphological Levels - Navickaitė, Eglė; Kudirka, Robertas (Vertimo studijos, 2024)
The article examines the lexical and morphological features of newspeak in Laimantas Jonušys’s Lithuanian translation of David Mitchell’s dystopian novel Cloud Atlas. The research material is drawn from an excerpt of the chapter “Teliūskas perkėla i visa paskum” (pp. 279–308) and its corresponding part in the original text (pp. 213–236). In the translation, the features of newspeak are conveyed through lexical and semantic neologisms, occasional and potential formations, as well as typical and atypical derivational variants. Additionally, literally translated and passive lexical layer words play distinctive roles. The findings demonstrate that formation by analogy and the recognizable variability of specifying lexical and morphological elements in relation to standard language contribute to a convincing representation of the dystopia’s artistic vision, effectively rendering the original newspeak and its post-apocalyptic impression.
Keywords: translation; dystopian newspeak; neology; morphology